2015
DOI: 10.1186/s12944-015-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cholesterol is associated with the depressive-like behavior in rats through modulation of the brain 5-HT1A receptor

Abstract: BackgroundLow serum cholesterol levels are related to an increased risk of depression and its serious consequences. However, the effect of central cholesterol on depressive disorder and its potential regulatory mechanism is poorly understood. Therefore, brain cholesterol in patients with depression may not only decrease the risk for developing this disease but also increase the beneficial effects of treatment for depression.MethodsIn current study, rats were exposed to chronic mild stress (CMS) for consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Indeed, it has been shown that increased HDL and omega-3 PUFAs could protect against depression-mediated inflammation [74,152]. The precise mechanics of inflammatory processes continues to place protein dysfunction as a key aspect of MDD pathophysiology, but the role of lipids is proving to be just as important, especially since protein function at the molecular level is largely determined by lipid function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it has been shown that increased HDL and omega-3 PUFAs could protect against depression-mediated inflammation [74,152]. The precise mechanics of inflammatory processes continues to place protein dysfunction as a key aspect of MDD pathophysiology, but the role of lipids is proving to be just as important, especially since protein function at the molecular level is largely determined by lipid function.…”
Section: Discussionmentioning
confidence: 99%
“…Low cholesterol content in cell membranes is associated with decreased density of 5-HT receptors measured in in vitro mouse analysis [72,73,74]. Sun et al exposed rats to chronic mild stress (CMS) for 28 days and showed significantly reduced total cholesterol level in the medial prefrontal cortex (mPFC) [74]. Chronic dietary supplementation reversed the behaviours induced by CMS.…”
Section: Cholesterolmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, accumulating evidence suggests that various psychiatric disorders including depression can be affected by the altered lipids levels (TC, TG, LDL, and HDL) . Lipids are found to be involved in the neuronal function of the brain, influencing emotional behaviours and mental disorders . Depression and elevated total cholesterol are identified as an independent and potent risk factor for cardiovascular disease .…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Lipids are found to be involved in the neuronal function of the brain, influencing emotional behaviours and mental disorders. 20 Depression and elevated total cholesterol are identified as an independent and potent risk factor for cardiovascular disease. 21 There is growing evidence that high TC levels may have influence on the serotoninergic activity in the brain and may be the cause of poor uptake of 5-HT from the bloodn.…”
Section: Discussionmentioning
confidence: 99%